The Profits of Power: Land Rights and Agricultural Investment in Ghana - Goldstein, Markus; Udry, Christopher (Journal of Political Economy, 2008)
We examine the impact of ambiguous and contested land rights on investment and productivity in agricultural in Akwapim, Ghana. We show that individuals who hold powerful positions in a local political hierarchy have more secure tenure rights, and that as a consequence they invest more in land fertility and have substantially higher output. The intensity of investments on different plots cultivated by a given individual correspond to that individual’s security of tenure over those specific plots, and in turn to the individual`s position in the political hierarchy relevant to those specific plots. We interpret these results in the context of a simple model of the political allocation of land rights in local matrilineages.